Mekanisme Pengangkatan Pemimpin Negara dalam Islam - Arip Purkon (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
This research examined the mechanisms for appointing state leaders in Islam. The research was conducted by studying the appointment of leaders since the time of the Prophet Muhammad PBUH, the caliphs Abu Bakr, Umar bin Khathab, Uthman bin Affan, Ali bin Abi Talib. In addition, it also studied the mechanisms for appointing state leaders in Saudi Arabia, Morocco, and Jordan which are considered Islamic countries. In Islamic history, the election of state leaders was carried out in different forms. This difference occurs based on considerations in accordance with the situation and conditions that occurred when the election of the leader was carried out. Islamic law only mentions the principles of leadership in general which must be used as a guide in selecting the country's leadership.Keywords: Al-Quran; Sunnah; Leader; Islam; Trust AbstrakPenelitian ini mengkaji tentang mekanisme pengangkatan pemimpin negara dalam Islam. Penelitian dilakukan dengan mengkaji pengangkatan pemimpin sejak masa Rasulullah, masa khalifah Abu Bakar, Umar bin Khathab, Utsman bin Affan, Ali bin Abi Thalib. Selain itu juga dikaji tentang mekanisme pengangkatan pemimpin Negara di Arab Saudi, Maroko dan Yordania yang dianggap sebagai negara Islam. Dalam sejarah Islam, pemilihan pemimpin negara dilakukan dalam bentuk yang berbeda-beda. Perbedaan tersebut terjadi didasarkan pada pertimbangan-pertimbangan sesuai dengan situasi dan kondisi yang terjadi saat pemilihan pemimpin tersebut dilakukan. Hukum Islam hanya menyebutkan prinsip-prinsip kepemimpinan secara umum yang harus dijadikan pedoman dalam pemilihan kepemimpinan negara.Kata Kunci: Al-Quran; Sunah; Pemimpin; Islam; Amanah